Local Curriculum in Basic Level Education: Cultural Connection Versus Academic Coherence - Sharma (Gyawali) , Bishnu (Pragyaratna प्रज्ञारत्न, 2024)
This study examines the dynamic friction that arises when local curriculum at the basic education level is implemented, balancing academic consistency with cultural connectedness. The objective of the study is to investigate strategies to preserve academic integrity and standards while incorporating local cultures into the basic education curriculum. I used post positivist research paradigm, with random sampling and Likert type questionnaire is used to collect the data from the respondents. One sample t- test is used in data analysis procedure. Insights from educators, legislators, and a range of case studies are included in this conversation, which emphasizes the advantages and difficulties of incorporating regional culture into basic education while upholding strict academic standards. Creating a diverse learning environment versus upholding academic coherence is a common point of debate in the discussion around the adoption of local curriculum in basic level. The relevance of both, their potential for balance, and their possible effects on the growth and learning of students are all examined. The difficulty of striking a balance between culturally relevant instruction and standardized academic coherence is being brought to light by the global effort to improve inclusivity and usefulness in education systems.